2019
DOI: 10.22271/ortho.2019.v5.i1d.32
|View full text |Cite
|
Sign up to set email alerts
|

A-prospective study of the outcome of closed intramedullary fixation of humeral shaft fractures treated with multiple K-wires in adults

Abstract: To evaluate the feasibility and efficacy of management of fracture of shaft humerus in adults by closed reduction internal fixation with the help of long K-wires followed by immobilization for 3 weeks in splint and then guarded mobilization till fracture united. Methods: This was a prospective longitudinal study. The subjects with fresh diaphyseal humeral shaft fractures without injury to the same limb, transverse/oblique fractures with a large butterfly fragment, comminuted fractures/segmental fragments and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Achieving a full range of motion for the elbow in all participants is another positive outcome, as it is essential for functional recovery. These findings are in line with the prospective study, which found excellent elbow movements in 93% of patients [13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Achieving a full range of motion for the elbow in all participants is another positive outcome, as it is essential for functional recovery. These findings are in line with the prospective study, which found excellent elbow movements in 93% of patients [13].…”
Section: Discussionsupporting
confidence: 92%
“…The majority of fractures in this study were transverse or oblique (77.8%), with spiral fractures being less common (22.2%). These findings can be compared with a prospective study, which typically describes transverse or oblique with butterfly fractures as the most common types of humeral shaft fractures [ 13 ]. The location, nature, and degree of the impact that caused the fracture determine the fracture type.…”
Section: Discussionmentioning
confidence: 99%